Bipolar spindle assembly - Karsenti, Eric (Henry Stewart Talks, 2009)
Mitosis, Spindle assembly, Self-organization, Chromosome segregation, Microtubule dynamics, Collective behavior of microtubule-motors systems, Reaction diffusion processes, Gradients of microtubule dynamics and nucleation, The Ran system in mitosis